THE EFFECTIVENESS OF USE THE KANJI CARDS IN KANJI SHOKYU LEARNING - Lispridona Diner; Dyah Prasetiani (Universitas Negeri Semarang, 2015)
Japanese character (hiragana, katakana, kanji, and romaji) is difficult for the students who learn Japanese as a foreign language, especially the kanji. Kanji has stroke order, and also Chinese and Japanese ways of reading. Moreover one character of kanji is presenting one meaning, thus the amount of kanji is massive. The informal interview conduct in some students on Semarang State University, Japanese Department, 2 semester, reveal that they got problems in memorizing the meaning and also the ways of reading and writing kanji. The reasons are there are too many kanji character and kanji compound they had to memorize in a short time during the class. It was not easy for them to memorize all the kanji. It was like memorizing the new vocabulary. Some words they didn’t familiar with will cause any further problems such as they didn’t know how to apply it into the sentence. Sometimes they ask the teacher, sometimes they didn’t. If they ask to the peer, they didn’t get the answer because the peer didn’t know either. Actually, the text book they use has reading and writing practice sections which is enough and proper to learn by themselves. But sometimes students need to make they own sentences in order to make their memory of kanji more lasting. Since the students admitted that they lacks of practice making sentences themselves nor with their peer, inside or outside the class, therefore, we conducted an quasi experiment in a class, using roundtable cooperative learning technique combine with kanji card in order to overcome the student’s problems mentioned above. This technique encourages students to: produce sentences which using the memorized kanji, working together in groups, students feel fun in learning kanji. nd But, this technique not quite suitable if we conduct it in a large class.